A feasibility study of combining solar/wind energy to power a water pumping system in Jordan's Desert/Al-Mudawwara village - Zakaria Al-Omari; Nour Khlaifat; Mike Haddad (Environmental and Sustainability Indicators)
Water availability and accessibility are the most significant challenges facing developing countries like Jordan, which is ranked as one of the world's worst countries in terms of water resources. In Jordan's isolated desert areas, where underground wells supply water for livestock and human consumption, water pumping systems (WPSs) are essential. Therefore, finding alternative energy sources is necessary to power underground WPSs. However, numerous diesel generator (DG) issues impact the energy supply. This article presents the design and evaluation of a hybrid renewable energy system (HRES) powering a WPS in an isolated desert region (Al-Mudawwara village/Ma'an governorate) with a daily demand of 40.71 kWh, which is economically viable, environmentally friendly, and sustainable. Using the HOMER simulation software, the most efficient scenario is determined considering the average monthly solar radiation, average wind speed of 3.79 kWh/m2 and 6.31 m/s, respectively, economic limitations, and the component's technical specifications. The net-present cost (NPC), cost of energy (CoE), and the percentage of renewable energy fraction (REF) and Greenhouse gas emissions (GHGE) are utilized as optimization criteria. The results obtained show that the scenario with minimum initial capital cost (ICC) and total NPC, respectively, was the one with DG/WT/storage batteries (SB) ($US 53,69) and ($US 59,611). The HRES (PV/WT/SBs) is the optimal scenario since it produces power at the lowest CoE ($US 0.241/kWh), leading to reliable energy and eliminating GHGE.